THE LABOR MARKET AND THE SKILLS NEEDS DEVELOPMENT AMONG ADULTS IN THE REPUBLIC OF NORTH MACEDONIA (Annual of the Faculty of Philosophy in Skopje, 2024)
In the rapidly evolving global economy, aligning labor market demands withskills needs development among adults is critical for sustainable economic growth andindividual career success. This alignment ensures that the workforce remains competitive,adaptable and capable of meeting industry requirements. A significant mismatchbetween labor market demands and available skills can lead to increased unemployment,underemployment, and diminished economic productivity. Addressing this gap necessitatesa comprehensive understanding of current and future labor market trends, coupledwith targeted educational and training programs.Adult education and continuous professional development play pivotal rolesin this context, enabling workers to acquire new skills and upgrade existing ones inresponse to technological advancements and changing job roles. Collaboration amongpolicymakers, educational institutions and industry stakeholders is essential to createresponsive training programs that reflect the dynamic nature of the labor market. Moreover,effective skills development strategies can enhance job satisfaction, increase earningpotential and reduce socio-economic inequalities. By fostering a culture of lifelonglearning and adaptability, societies can better prepare their workforces for the challengesof the future, ensuring economic resilience and improved quality of life for individuals.This strategic approach ultimately benefits for both employers and employees, promotinga more inclusive and robust labor market.
Keywords: labor market; skills; education; training; lifelong learning